Radiation Grafting of Adsorbent for Improving Nickel Adsorption Capacity from Aqueous Solutions: Chitosan/ Poly (Vinyl Alcohol) Radiation Grafted with Acrylic Acid - Nasrin Sheikh; Shohreh Kianfar (مجله علوم و فنون هسته‌ای, 2014)
groups bonded to the polymer. The aim of this study was to investigate the effect of radiation grafting of acrylic acid on the crosslinked Chitosan/poly (vinyl alcohol) adsorbent film to improve the absorption of nickel from aqueous solutions. For this purpose, acrylic acid (AA) monomer was grafted on the crosslinked Chitosan/poly (vinyl alcohol) film by using gamma radiation. The effect of radiation dose on the grafting percentage was studied. The chemical structure of the adsorbent was determined by FTIR spectroscopy. Nickel adsorption experiments were carried out as a function of the pH of media, irradiation dose and initial concentration of Ni solution by means of batch method. Adsorption modeling was made by Langmuir and Dubinin-Radushkevich isotherms and the experimental measurements were well fitted to the Langmuir adsorption model. Finally, the results showed the nickel adsorption improvement on the crosslinked Chitosan/ poly (vinyl alcohol) film by radiation grafting of acrylic acid as an oxygen-containing functional group.